TOWARD VICTIM-ORIENTED RESTITUTION IN JOB RECRUITMENT FRAUD FROM THE PERSPECTIVE OF DECISION NUMBER 220/PID.B/2024/PN.BJN (International Journal of Cultural and Social Science, 2026)
This study examines whether Court Decision No. 220/Pid.B/2024/PN.Bjn reflects victim-oriented restitution in adjudicating job recruitment fraud. This normative legal research employs statutory, conceptual, and case approaches to analyze the court decision alongside the relevant victim protection regulations, namely Law No. 31 of 2014, Government Regulation No. 7 of 2018, and Supreme Court Regulation (PERMA) No. 1 of 2022. The analysis shows that although the panel of judges explicitly acknowledged the victims’ material losses of Rp6,000,000.00 and Rp14,700,000.00, the verdict imposed only imprisonment and contained no order of restitution. This finding exposes a normative gap between Indonesia’s victim protection and judicial practice. The study recommends that restitution be operationalised from the investigation stage, included in the prosecutor’s indictment, explicitly considered and granted by judges, and supported by the Witness and Victim Protection Agency (LPSK). The article thus advances a shift from a perpetrator-oriented criminal justice system toward one that genuinely centres victim recovery.